2020
DOI: 10.1186/s13034-020-00334-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between acculturation and mental health of 1st generation immigrant youth in a representative school survey: does gender matter?

Abstract: Background: Although gender plays a pivotal role in the psychological adaptation of immigrant youth, its association with acculturation strategy and mental health among 1st generation immigrant adolescents are still scarce and inconsistent. Therefore, the purpose of the current study was to investigate gender-related differences in acculturation patterns and their association with mental health (internalizing and externalizing problems). Methods: Self-reported data of immigrant adolescents (N = 440) aged betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
4
12
0
Order By: Relevance
“…An interpretation could be that social and cultural conditions might be more decisive than time in their adjustment to the new context ( Raabe and Beelmann, 2011 ; Hernando et al, 2013 ; Titzmann et al, 2015 ). Results also showed that immigrant girls presented higher levels of self-efficacy in mixing satisfactorily with other cultures, which coincides with previous reports ( Berry et al, 2006 ; Motti-Stefanidi et al, 2008 ; Güngör and Bornstein, 2013 ; Klein et al, 2020 ) that have claimed that girls are more likely to develop positive attitudes toward intercultural exchanges than boys, presenting higher self-efficacy in social interactions with different others ( Caprara et al, 2004 ; Bagci, 2018 ). Gender differences were also found regarding immigrant students’ school satisfaction, agreeing with studies which have established that girls tend to develop a better adjustment to school contexts and tasks than did boys, including immigrant females ( Verkuyten and Thijs, 2002 ; Berry et al, 2006 ; Liu et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An interpretation could be that social and cultural conditions might be more decisive than time in their adjustment to the new context ( Raabe and Beelmann, 2011 ; Hernando et al, 2013 ; Titzmann et al, 2015 ). Results also showed that immigrant girls presented higher levels of self-efficacy in mixing satisfactorily with other cultures, which coincides with previous reports ( Berry et al, 2006 ; Motti-Stefanidi et al, 2008 ; Güngör and Bornstein, 2013 ; Klein et al, 2020 ) that have claimed that girls are more likely to develop positive attitudes toward intercultural exchanges than boys, presenting higher self-efficacy in social interactions with different others ( Caprara et al, 2004 ; Bagci, 2018 ). Gender differences were also found regarding immigrant students’ school satisfaction, agreeing with studies which have established that girls tend to develop a better adjustment to school contexts and tasks than did boys, including immigrant females ( Verkuyten and Thijs, 2002 ; Berry et al, 2006 ; Liu et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…An interpretation could be that social and cultural conditions might be more decisive than time in their adjustment to the new context (Raabe and Beelmann, 2011;Hernando et al, 2013;Titzmann et al, 2015). Results also showed that immigrant girls presented higher levels of self-efficacy in mixing satisfactorily with other cultures, which coincides with previous reports (Berry et al, 2006;Motti-Stefanidi et al, 2008;Güngör and Bornstein, 2013;Klein et al, 2020) that have claimed that girls are more likely to develop positive attitudes toward FIGURE 3 | Simple mediation model. Cultural self-efficacy's effect on the relationship between prejudice and school satisfaction in Chilean students.…”
Section: Discussionsupporting
confidence: 82%
“…As migration background in Europe is not, in general, a predictor for higher behavioral or emotional problems [ 8 ], potential differences among immigrant groups are required. As a few examples, the country of origin, reasons for immigration, gender, acculturation style [ 51 ], attitudes towards immigrants among the majority of the population [ 9 ], immigrant policies [ 7 ], and social contexts—e.g., school culture—within which adolescents are living [ 4 ] should be analyzed in future studies. Although individuals with migration background and those without migration background did not differ with respect to gender and age, they differed with respect to region and school type.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly children with low socioeconomic status and preexisting mental health problems may be exposed to cumulative risks. This assumption is based on a solid body of previous research demonstrating that a low socioeconomic status of children [9][10][11], low parental education and migration status [12,13] are risk factors for mental health problems among children. Also when experiencing home confinement, it can be assumed that children living in small apartments are more stressed-concluding from the literature indicating that limited living space can affect mental health [14].…”
Section: Supplementary Informationmentioning
confidence: 99%